2009
DOI: 10.1080/13552070903009668
|View full text |Cite
|
Sign up to set email alerts
|

Paying back comes first: why repayment means more than business in rural Senegal

Abstract: Giving small loans to women has become a mainstay in development practitioners' toolkits. Using data collected for Oxfam America's Saving for Change (SFC) project, this article argues that repayment of micro-credit cannot be used as a measure of micro-enterprise development per se. Instead, repayment signals the presence of peer pressure, loan sharing and remittance payments in the studied setting. This conclusion is borne through an ethnographic approach, which focuses on who accesses loans, how people who ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 18 publications
0
14
0
1
Order By: Relevance
“…On the other hand, evidence of inclusion and solidarity is equally critical, particularly where critics of microfinance emphasize exclusion. Despite significant participation of very poor people, several authors argue that the existence of entry fees in women's organizations coupled with the fear of default under joint liability necessarily exclude the poor (Duffy-Tumasz, 2009;LourencoLindell, 2002). Concerns about default go to the heart of the logic behind group microcredit schemes, the idea that shared responsibility attaches social consequence to default, while strengthening the social capital of members whose incentives become tied to the success of the group (Buss, 2005).…”
Section: (B) Women's Organizations As Microfinance Institutions and Smentioning
confidence: 98%
“…On the other hand, evidence of inclusion and solidarity is equally critical, particularly where critics of microfinance emphasize exclusion. Despite significant participation of very poor people, several authors argue that the existence of entry fees in women's organizations coupled with the fear of default under joint liability necessarily exclude the poor (Duffy-Tumasz, 2009;LourencoLindell, 2002). Concerns about default go to the heart of the logic behind group microcredit schemes, the idea that shared responsibility attaches social consequence to default, while strengthening the social capital of members whose incentives become tied to the success of the group (Buss, 2005).…”
Section: (B) Women's Organizations As Microfinance Institutions and Smentioning
confidence: 98%
“…As marriage to men who work abroad becomes an increasingly attractive strategy for women to achieve financial security, long periods of separation between transnationally located spouses are not uncommon (Hannaford, 2014; Hannaford & Foley, 2015). In a context where a third of married women are in polygamous unions (ANSD, 2012), not all women live in the same household as their spouse (Duffy-Tumasz, 2009). In both monogamous and polygamous marriages, shifts in women’s status within the relationship may influence their perceptions of pregnancy desirability (Bledsoe, 2002).…”
Section: The Production Of Post-abortion Care Datamentioning
confidence: 99%
“…Research elsewhere notes similar remittance‐driven repayment strategies among households borrowing from microfinance organizations, particularly in areas of high out‐migration or where remittances are common. In Senegal, Duffy‐Tumasz () found that many borrowers in Oxfam's Savings for Change microcredit programme paid back loans via remittances from friends and relatives abroad. This, she argued, suggests that ‘microcredit is operating as a cheap source of credit not for business, as much as to sustain villagers given the uneven arrival of remittance payments’.…”
Section: Borrowing and Migration: Pathways And Possibilitiesmentioning
confidence: 99%
“…In Andhra Pradesh, India, Taylor (: 497) argues that microcredit forces the most vulnerable deeper into contract labour, with the ‘compulsions of indebtedness’ serving as ‘primary motivation for migration of all forms’. Similarly, in Senegal, Duffy‐Tumasz () describes how households regularly use micro‐credit as a cash advance on forthcoming remittances from relatives living abroad. Thus there is evidence spanning a variety of contexts to suggest that migration and expanded access to credit can be mutually enabling processes.…”
Section: Theorizing Migra‐loansmentioning
confidence: 99%